FOOD DIPLOMACY IN MUNICIPAL POLICIES FOR THE SOCIAL INTEGRATION OF IMMIGRANTS: GAZIANTEP METROPOLITAN MUNICIPALITY (Third Sector Social Economic Review, 2025)
Food has a solidarity value for communities as a collective that goes beyond nutritional needs and habits. In this respect, many studies highlighting the relationship between food culture and migration allow for a deeper study of gastronomy as a discipline. The importance of this study is that it evaluates the impact of food culture on the phenomenon of migration from a different perspective, addressing the relationship between food culture and migration within the diplomatic relations of local governments. Thus, the phenomenons of migration, food and diplomacy are discussed together at the urban level. The aim of the study is to examine the impact of food diplomacy activities in the context of local governments' migration policies. The study covers the migration and food diplomacy activities of Gaziantep Metropolitan Municipality. The study was conducted using the document analysis method through literature. Within the results of the study, it was found that the impact of local governments' food diplomacy activities on their migration policies has important results on the employment and cultural interaction of immigrants living in the city.
Keywords: Food Diplomacy; Gastronomy; Migration; Local Governments; City Diplomacy.